Comparison of femoral neck system versus cannulated screws for treatment of femoral neck fractures: a systematic review and meta-analysis - Jiabao Jiang; Jialei Chen; Fei Xing; Hao Liu; Zhou Xiang (BMC Musculoskeletal Disorders, 2023)
Abstract Background Recently, some studies on the efficacy of the femoral neck system (FNS) in treating femoral neck fractures (FNFs) have been published. Therefore, a systematic review was performed to clarify the efficacy and safety of FNS versus cannulated screws (CS) for the treatment of FNFs. Method The PubMed, EMBASE, and Cochrane databases were systematically searched for studies comparing FNS and CS fixations in FNFs. Intraoperative indicators, postoperative clinical indicators, postoperative complications, and postoperative scores were compared between the implants. Results A total of eight studies were included in the study, involving 448 FNFs patients. The results showed that patients in FNS group were significantly lower than the CS group in the number of X-ray exposures (WMD = -10.16; 95% CI, -11.44 to -8.88; P < 0.001; I2 = 0%), fracture healing time (WMD = -1.54; 95% CI, -2.38 to -0.70; P < 0.001; I2 = 92%), length of femoral neck shortening (WMD = -2.01; 95% CI, -3.11 to -0.91; P < 0.001; I2 = 0%), femoral head necrosis (OR = 0.27; 95% CI, 0.08 to 0.83; P = 0.02; I2 = 0%), implant failure/cutout (OR = 0.28; 95% CI, 0.10 to 0.82; P = 0.02; I2 = 0%), and Visual Analog Scale Score (WMD = -1.27; 95% CI, -2.51 to -0.04; P = 0.04; I2 = 91%). And the Harris Score was significantly higher in the FNS group than in the CS group (WMD = 4.15; 95% CI, 1.00 to 7.30; P = 0.01; I2 = 89%). Conclusions Based on this meta-analysis, FNS shows better clinical efficacy and safety in treating FNFs compared to CS. However, due to the limited quality and number of included studies and the high heterogeneity of the meta-analysis; large samples and multicenter RCTs are needed to confirm this conclusion in the future. Level of evidence II, Systematic review and Meta-analysis. Trial registration PROSPERO CRD42021283646.